Educational Leadership in Islamic Boarding Schools in the Perspective of K.H. Abdullah Syukri Zarkasyi - Azizah Hanum OK; Junaidi Arsyad; Iqbal Syafi'i (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The phenomenon of the decline of many Islamic boarding schools in Indonesia is caused by the inability of the descendants of the Kiai or pesantren founders to continue the relay of educational leadership. K.H. Abdullah Syukri Zarkasyi with his ideas and thoughts provided a solution to overcome the educational leadership crisis. This study aims to analyze educational leadership in Islamic boarding schools from the perspective of K.H. Abdullah Syukri Zarkasyi and its relevance to UURI No. 18 of 2019 concerning Islamic Boarding Schools. This research is qualitative research with the type of library research using a character study approach. The results of this study are: (1) Educational leadership in Islamic boarding schools in the perspective of K.H. Abdullah Syukri Zarkasyi is summarized in the following four points: First, the nature of the pesantren leadership as a central figure, caregiver, and protector of the students, teachers, and staff. The pattern of educational leadership is transformational and collective, not individual or charismatic. Second, there are seven roles of an educational leader in an Islamic boarding school. Third, pesantren leaders must have 14 qualifications that are indicators of their feasibility, professionalism, and competence. Fourth, the leader regeneration program can be carried out with seven methods. (2) Thoughts of K.H. Abdullah Syukri Zarkasyi have relevance to UURI No. 18 of 2019 concerning Islamic Boarding Schools.